Redes de interacciones entre plantas y aves frugívoras en el Parque Universitario de Educación Ambiental y Recreacional (PUEAR), Loja, Ecuador - Robles Tandazo, Ronaldo Rolando (2024)
Plant-animal ecological interactions are the fundamental basis for understanding the dynamics and functioning of ecosystems. The mutual relationship between frugivorous birds and plants favors natural regeneration of ecosystems through seed dispersal; however, this service provided by birds may be affected by fragmentation and changes in the environment, due to anthropic activities. The present study focused on understanding and evaluating the structure of the interaction networks between plants and frugivorous birds in three types of vegetation cover in PUEAR: natural forest, forest plantations and scrub-moor. For the record of interactions, focal observation trees (in fruiting) were used on each type of plant cover. The data collected were used to construct interaction networks using a quantitative matrix. Five indices of the network of each plant cover were calculated: nesting, connectance, modularity, robustness and asymmetry. The connectance index was higher in scrub-paramo (0.50) compared to other coverages. Nesting and robustness were low for all three coverages; however, natural forest presented the highest value for both indices (0.30 and 0.38 respectively). Modularity was higher in forest plantations (0.53). As for asymmetry, it was positive for all three types of plant cover. Although the rates did not vary widely in each type of plant cover, the small difference is attributed to the availability of plants in fruiting and the greater number of interactions between the two species, enabling natural forest to be more resilient to disturbance.